Culture of peace: A construction from education - Hernandez Arteaga, Isabel; Luna Hernández, Jose Alberto; Cadena Chala, Martha Cecilia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
This review article made possible a theoretical tracing about the relationship between the construction of peace culture and the transformation of education in an unsafe and uncertain world. Objective: to examine conceptual tendencies about peace, culture of peace, construction of peace culture facing the responsibility of education in this context. Methodology: Based on the hermeneutical approach and the interpretative research, a bibliographical documentary review of 57 texts was carried out, including articles, books and documents; all of them dealing with the construction of peace culture. This methodology required the elaboration of review cards and triangulation matrices which allowed the interpretation of the information. Results: it is assumed the complexity of the concept of peace, this is: the negative peace, the positive peace, and the neutral peace. It is recognized that in the culture of peace, conflicts become development engines. Education in and for conflict is understood as an instrument of social change and as an opportunity to learn how to build relationships; citizens within a climate of respect and dignity can achieve peace. Therefore, education must be a protagonist in the construction of a culture of peace from the formation of values in sustainable development scenarios. Conclusion: The construction of peace culture is possible from education with human sense, formation in values and the development of critical thinking in search of social justice.